Prospective observational study on the impact of the 21-gene assay on treatment decisions and resources optimization in breast cancer patients in Lombardy: The BONDX study. (August 2020) - Zambelli, Alberto; Simoncini, Edda; Giordano, Monica; La Verde, Nicla; Farina, Gabriella; Torri, Valter; Colombo, Giorgio; Piacentini, Giulia; Fotia, Vittoria; Vassalli, Lucia; Pugliese, Palma; Poletti, Paola; et al.
Abstract: Purpose: Adjuvant treatment decisions in early breast cancer (eBC) have traditionally been driven by risk stratification based on clinical and pathological risk factors. The 21-gene Oncotype DX® assay has been validated as a predictive test for benefit from adjuvant chemotherapy (CT), hence assessing its impact in clinical decisions is of high interest. The objective of this study was to estimate the rate of adjuvant treatment decision modification impacted by the Recurrence Score® result, and the consequent budget impact. Methods: The study was a multicentre, prospective, real-life experience in Lombardy (Italy) including consecutive patients with T1–T3, N0–N1a, and ER+/HER2-eBC with clinical-pathologic "intermediate risk" of relapse. The change in treatment recommendations was assessed before and after availability of Recurrence Score result. A budget model evaluated the implications of 21-gene testing in the study population. Results: The overall proportion of CT recommendations was reduced from 24.6% to 15.2% after 21-gene testing, with a major impact in patients initially considered for CT plus hormone therapy (CHT). In these patients, the total budget was reduced, leading to a net saving of -€81, 017. The greater the physician propensity to prescribe CHT, the higher the potential savings for the health system from sparing CT in most tested patients. Conclusions: Our real-life experience suggests that all intermediate-risk ER+/HER2-eBC patients who are initially deemed candidates for CHT should be tested with the 21-gene test. The potential to spare CT in at least half of them offers relevant advantages for patients and national health services. Highlights: The 21-gene assay is validated to guide adjuvant treatment decisions in eBC. We identify patients in which 21-gene testing led to best performance in CT sparing. Testing this patient group obtains the best performance in cost-benefit-ratio. Lombardy approves the 21-gene assay for patients at clinical intermediar risk.